Instagram-Based Learning Media: Improving Student Motivation and Learning Outcomes in Reaction Rate - Widarti, Hayuni Retno; Rokhim, Deni Ainur; Yamtinah, Sri; Shidiq, Ari Syahidul; Baharsyah, Allykha (SCAD Independent, 2024)
This study aimed to determine the improvement of student motivation and learning outcomes in reaction rate using Instagram-based learning media. The quasi-experiment method was used in this study. Instruments in the form of questionnaires were used to assess student motivation, and pre-tests and post-tests were used to measure student learning outcomes. This research was conducted at a high school in Malang City, East Java, Indonesia. A total of 33 students participated in the experimental and 28 in the control classes. The learning process was carried out for three meetings using the Problem-Based Learning model with Instagram-based learning media as the independent variable. The results showed that the average N-gain value in the experimental class was 0.71. The control class was 0.55 with a significance value of 0.004, proving that using Instagram as a learning medium can improve students’ understanding of reaction rate content and motivate them to learn more.